Case Report: Cytoreductive Surgery and Hyperthermic Intraperitoneal Chemotherapy Application in Intraperitoneally Disseminated Inflammatory Myofibroblastic Tumor and in the Youngest Patient in the World: New Indication and Modification of Technique - Garnier, Hanna; Murawski, Maciej; Jastrzebski, Tomasz; Pawinska-Wasikowska, Katarzyna; Balwierz, Walentyna; Sinacka, Katarzyna; Gorecki, Wojciech; Izycka-Swieszewska, Ewa; Czauderna, Piotr (Frontiers in Surgery, 2021)
Introduction: Peritoneal metastases occur in cancers that spread to the peritoneal cavity and indicate the advanced stage of the disease. In children they are mainly seen in sarcomas, Gastrointestinal Stromal Tumors and primary disseminated ovarian tumors. Inflammatory Myofibroblastic Tumor (IMT) is a very rare lesion, characterized by an unpredictable clinical course. The absorption of chemotherapeutic agents through the peritoneal-plasma barrier (PPB) is minimized, thus HIPEC procedure limits the systemic exposure to chemotherapy and permits the administration of its higher doses. The main purpose of HIPEC is to remove the visible macroscopic disease in order to achieve complete cytoreduction (CRS). HIPEC Procedure in Children: Several papers deal with the CRS and HIPEC in children and adolescents, however pediatric experience is still limited. Thus far, the HIPEC procedure has been carried out on patients over 2 years old. The most common indication for the surgery and the best outcome was experienced by patients with desmoplastic small round cell tumor (DSRCT). Most patients received intraperitoneal cisplatin. HIPEC Modification: A 5-month-old infant was admitted to the Department of Pediatric Oncology due to the abdominal distention and blood in the stool. The Computed Tomography (CT) revealed a solid-cystic mass in the right abdominal area. The primary tumor and numerous peritoneal metastasis were removed and the Inflammatory Myofibroblastic Tumor (IMT) was diagnosed. The patient underwent subsequently CRS and modified HIPEC procedure. To avoid overheating of the infant, the intraperitoneal normothermic chemoperfusion was performed. Due to the low body weight a modified dosage of intraperitoneal doxorubicin was used. The child underwent standard postoperative chemotherapy and received crizotinib therapy. At 12 months follow-up since treatment completion the patient remains in complete remission. To our knowledge this is the youngest patient, the only infant and the first pediatric patient with IMT who underwent the modified HIPEC procedure in the world. Conclusions: CRS and HIPEC is technically possible also in infants. For its safe course patients selection and technique modification are necessary. Use of HIPEC should be also considered in intraperitoneally disseminated IMT. A complete cytoreductive surgery as the first HIPEC step seems to be the key factor in survival.